1973
DOI: 10.1002/ps.2780040103
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of tri‐allate volatility

Abstract: The volatility of tri‐allate from different formulations when mixed with 2 soils containing water at 2%, 6% and field capacity was estimated in the laboratory. Volatility increased with increasing water content in each case. It was generally highest from an emulsifiable concentrate and lowest from a granule formulation with that from unformulated tri‐atlate intermediate. In a greenhouse experiment rates of loss of tri‐allate from a dry soil were similar for both emulsifiable concentrate and granule formulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…All three tested herbicides were deactivated after exposure on a wet soil surface. Greater losses on moist than on dry soil have been reported for volatile herbicides (Gray & Weierich, 1965;Hance, Holroyd & McKone, 1973;Horowitz, 1966;Parochetti, Hein & Colby, 1971;Parochetti and Warren, 1966) and for relatively low volatile herbicides (Kearney, Sheets & Smith, 1964). Several factors are probably involved: due to competition between the herbicide and water for adsorptive sites, a smaller fraction of the applied herbicide is adsorbed in moist than in dry soil; the upward movement of evaporating water maintains the herbicide near the surface and exposed to factors of dissipation; in the moist soil microbiological processes start to degrade the herbicide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three tested herbicides were deactivated after exposure on a wet soil surface. Greater losses on moist than on dry soil have been reported for volatile herbicides (Gray & Weierich, 1965;Hance, Holroyd & McKone, 1973;Horowitz, 1966;Parochetti, Hein & Colby, 1971;Parochetti and Warren, 1966) and for relatively low volatile herbicides (Kearney, Sheets & Smith, 1964). Several factors are probably involved: due to competition between the herbicide and water for adsorptive sites, a smaller fraction of the applied herbicide is adsorbed in moist than in dry soil; the upward movement of evaporating water maintains the herbicide near the surface and exposed to factors of dissipation; in the moist soil microbiological processes start to degrade the herbicide.…”
Section: Resultsmentioning
confidence: 99%
“…Dissipation through photodecomposition and volatilization can reduce severely the activity of herbicides which remain exposed on the soil surface, especially in a warm climate. Since soil conditions affect the rate of dissipation of herbicides (Gray & Weierich, 1965;Hance, Holroyd & McKone, 1973;Horowitz, 1966;Parochetti & Warren, 1966, 1968, suitable conditions of the top soil at the time of application or thereafter, could minimize the loss of herbicide until it is leached into the soil and activated by rain or irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…The half-lives look very short for the more lipophilic compounds, but agree with experimental results. Woodrow et al (1986) found that high rates of herbicidal oils evaporated with t\ less than an hour and Hance et al (1973) found 50% loss of tri-( Tb % 400 °C and log Aow % 4) in 3 days from wet soil at 20 °C.…”
Section: Volatilization From Soilmentioning
confidence: 99%
“…Banting (1961) indicated that triallate vapors may be involved in the herbicidal activity of soil-incorporated triallate . The volatility of triallate is lower with the GR than EC forms and is the lowest with the GR form in dry soil (Hance et al 1973 Nitrogen is equally available to wheat regardless of the method of application.…”
mentioning
confidence: 90%